Soluble MICA and anti-MICA Antibodies as Biomarkers of Nasopharyngeal Carcinoma Disease. (3rd July 2020) - Ben Chaaben, Arij; Ouni, Nesrine; Douik, Hayet; Ayari, Fayza; Abaza, Hajer; Mamoghli, Tesnim; Harzallah, Latifa; Fortier, Cathy; Boukouaci, Wahid; Krishnamoorthy, Rajagopal; Charron, Dominique; Gara, Sonia; et al.
ABSTRACT: The MHC class I chain-related molecule A (MICA) is a ligand for the activating natural killer (NK) cell receptor NKG2D. A part from its genetic diversity, MICA is characterized by the presence of membrane-bound and soluble isoform (sMICA) and by the propensity to elicit antibody-mediated allogeneicity (MICA Abs). Altogether such properties are important in the cancer setting. Here, we investigated whether MICA polymorphism, serum level of sMICA and MICA antibodies (Abs) may influence nasopharyngeal carcinoma (NPC) risk. 274 NPC naïve of treatment patients and 275 healthy individuals, all originating from Tunisia were included and genotyped. Among them, 160 sera from patients and 51 from controls were analyzed for the sMICA level by ELISA and were tested for the presence of MICA Abs by Luminex assay. The statistical analysis showed that: (1) we extend and confer our previous finding concerning Val/Val association with risk of NPC ( p = .02, OR = 1.56; 95%CI [1.12–2.11]). (2) The higher level of sMICA characterized patients advanced stage of the disease. (3) The 18 (78%) of patients having MICA Abs exhibit all a non-advanced stage of the tumor extension at presentation. MICA129 Met /Val, sMICA and MICA Abs could be potential biomarkers of prediction, the diverse staging of NPC and hence prognostic and treatment.